Pengaruh Burnout Dan Beban Kerja Terhadap Kinerja Perawat Rawat Inap RS â€œXâ€ Pekanbaru - Sandora, Meri; Fahril, Nadia (Eko dan Bisnis: Riau Economic and Business Review, 2023)
This research was conducted at the â€œXâ€ Hospital Pekanbaru. The purpose of this study was to determine the effect of burnout and workload on the performance of inpatient nurses at the â€œXâ€ Hospital Pekanbaru, either partially or simultaneously. The population in this study were all Inpatient Nurses at the â€œXâ€ Hospital, totaling 88 nurses and the sample used in this study was 88 people. The method of determining the sample in this study uses a saturated sampling method (census). The data used are primary data and secondary data. The data analysis method used is descriptive analysis method and quantitative analysis method. The results showed that partially burnout had an effect on the performance of inpatient nurses at the â€œXâ€ Hospital Pekanbaru. Workload partially affects the performance of Â inpatient nurses at the â€œXâ€ Hospital Pekanbaru. Simultaneously burnout and workload have an influence on the performance of inpatient nurses at the â€œXâ€ Hospital Pekanbaru, while the magnitude of the effect is 61.9%, while the rest (38.1%) is influenced by other variables not examined in this study